Voice coil motor, magnetic circuit configuration assembly for voice coil motor and manufacturing method thereof

By forming a multi-layer structure of metal electroplating layer and oxide layer on rare earth sintered magnets, the problems of damage to permanent magnets in low-pressure hydrogen and deterioration of magnetic properties are solved, and the durability of voice coil motors and data read and write accuracy are achieved.

CN119181389APending Publication Date: 2024-12-24SHIN ETSU CHEMICAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410810569.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-02-27
Filing Date
2024-06-21
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

In a low-pressure hydrogen atmosphere, permanent magnets are easily damaged due to hydrogen embrittlement, resulting in deterioration of magnetic properties and cannot be used in the storage device for a long time.

Method used

Rare earth sintered magnets with metal electroplating layer, metal oxide layer or metal nitride layer are used to form a multi-layer structural coating to improve the anti-hydrogen corrosion ability of the magnets and prevent damage and deterioration of magnetic properties.

Benefits of technology

It effectively prevents the magnet from breaking or rupturing in a low-pressure hydrogen environment, maintains the stability of magnetic properties, and ensures the long-term use of the voice coil motor and the accuracy of data reading and writing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004906044230000011
    Figure HDA0004906044230000011
  • Figure HDA0004906044230000012
    Figure HDA0004906044230000012
  • Figure HDA0004906044230000021
    Figure HDA0004906044230000021
Patent Text Reader

Abstract

A magnetic circuit configuration assembly for a VCM includes a pair of yokes, a pair of magnets disposed on inner surfaces of the yokes, and a support member or support pillar maintaining a gap between the magnets to fix the yokes to each other, the magnets being rare earth sintered magnets having surfaces coated thereon, the composition of the magnet is composed of, by weight, 28% to 34% of R (R is one or more rare earth elements selected from Nd, Pr, Dy, Tb, Ce, La and Gd), 2% or less of Co, 0.5% to 2% of B, 2% or less of at least one element selected from Ni, Nb, Al, Ti, Zr, Cr, V, Mn, Mo, Si, Sn, Ga, Cu and Zn as an additive, and the balance Fe, and the coating includes a metal plating layer of a predetermined thickness and a metal oxide layer and / or a metal nitride layer of 0.01 [mu] m to 2 [mu] m.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a voice coil motor, a magnetic circuit configuration component for the voice coil motor, and a manufacturing method of the magnetic circuit configuration component. Background Art

[0002] A voice coil motor (hereinafter also referred to as VCM) is a magnetic circuit component for driving an actuator in a hard disk drive (hereinafter also referred to as HDD). Generally, during the operation of the HDD, when current flows through a coil provided in the actuator, the actuator moves to a specific position on a magnetic medium by the Lorentz force, and data is read from and written to the magnetic medium by using a magnetic head at the tip of the actuator.

[0003] As a magnetic medium for reading and writing data by the VCM in this manner, in addition to a disk-shaped magnetic disk as disclosed in Patent Document 1, there is an embedded magnetic tape wound and rewound by two reels as disclosed in Patent Document 2, etc. A memory using an embedded magnetic tape as in Patent Document 2 is called a magnetic tape memory. In the VCM, when an electric current passes through a coil in a magnetic field of a permanent magnet, a force is generated in a direction perpendicular to the magnetic field in the coil, and a reciprocating motion can be performed on the coil.

[0004] On the other hand, as a permanent magnet, in Patent Document 3 and Patent Document 4, as a rare earth sintered magnet that can be used for motors, etc. without causing hydrogen embrittlement even in a hydrogen atmosphere, a rare earth sintered magnet and a method for manufacturing the same are described, wherein the rare earth sintered magnet is composed of: 20 wt % to 35 wt % of R (R is one or two or more types of rare earth elements selected from Nd, Pr, Dy, Tb and Ho), 15 wt % or less of Co, 0.2 wt % to 8 wt % of B, 8 wt % or less of at least one type of element selected from Ni, Nb, Al, Ti, Zr, Cr, V, Mn, Mo, Si, Sn, Ga, Cu and Zn as an additive, and the remainder of Fe and unavoidable impurities, wherein a metal oxide layer and / or a metal nitride layer is provided on the surface of the rare earth sintered magnet directly or through n layers (n is an integer and n≥1) of metal electroplating layers.

[0005] The "motor" described in Patent Document 3 and Patent Document 4 is completely different from VCM. As described in Non-Patent Document 1, in the case of developing an electromagnetic diaphragm blower in order to put a hydrogen cycle blower of a fuel cell system into practical use, a problem arises that a component using a permanent magnet in the blower becomes brittle in an assumed use environment. At the time when Patent Document 3 and Patent Document 4 were filed, research on the supply power of hydrogen fuel was already active in order to realize a hydrogen energy society, and a problem arose that a permanent magnet mounted on a rotating electric machine deteriorated due to exposure to hydrogen. Patent Document 3 and Patent Document 4 relate to a rare earth sintered magnet mounted on such a rotating electric machine. Reference Documents List Patent Literature

[0006] Patent Document 1: JP 2009-140524A Patent Document 2: JP 2020-129424A Patent Document 3: JP 2003-257721A Patent Document 4: JP 2003-257768A Non-patent literature

[0007] Non-patent document 1: NEDOWM (NEDO Web Magazine), "Development of blower for innovative fuel cell system that is indispensable for realizing hydrogen society", November 2016, (URL: https: / / webmagazine.nedo.go.jp / practical-realization / articles / 201701techn o-takatsuki / ) Summary of the invention Problems to be solved by the present invention

[0008] As described in Patent Documents 1 and 2, it is necessary to seal a storage device (such as an HDD or a tape storage) by filling the interior of a housing with helium in order to reduce the vibration of a magnetic head or a magnetic disk. In addition, in view of the high cost of helium and the need for a gas with a lower density, it is necessary to use hydrogen instead of helium. In addition, the VCM used in the storage device includes a permanent magnet as described above. As described in Patent Documents 3 and 4, it has been pointed out that when a permanent magnet is exposed to a high-pressure hydrogen atmosphere for a long time, hydrogen embrittlement is caused, and the material is broken, cracked or crushed.

[0009] In the case where the housing of a storage device (such as an HDD) is filled with hydrogen, the VCM is placed in a low-pressure hydrogen atmosphere, unlike the case of the rotating electrical machines of Patent Documents 3 and 4. Patent Documents 3 and 4 describe that the crushing and the like hardly affect the magnetic properties of the permanent magnet itself, and as a comparative example, a test sample without a metal oxide layer (which is a feature of the invention of the document) is described as being crushed into pieces in a 10 MPa hydrogen test, and no description is given of changes in the magnetic properties of the permanent magnet exposed to the hydrogen atmosphere.

[0010] The present inventors tested the resistance of permanent magnets to low-pressure hydrogen when VCM was exposed to the low-pressure hydrogen atmosphere for a long time, and surprisingly found that although damage (such as chipping or cracking) did not occur to a certain extent even for permanent magnets having only a metal plating layer without a metal oxide layer (which is a feature of the present invention described in Patent Documents 3 and 4), the magnetic properties of the permanent magnets deteriorated without such damage and the permanent magnets could not withstand use in the VCM.

[0011] Therefore, the present invention is made in view of the above-mentioned problems, and an object of the present invention is to provide a voice coil motor, a magnetic circuit configuration component for a voice coil motor, and a manufacturing method of the magnetic circuit configuration component, wherein the voice coil motor can be prevented from being damaged (such as chipping or cracking) and prevented from deteriorating magnetic properties even when exposed to a low-pressure hydrogen atmosphere for a long time. Means used to solve problems

[0012] In order to achieve the above-mentioned object, a voice coil motor, a magnetic circuit configuration component for a voice coil motor, and a method for manufacturing the magnetic circuit configuration component according to the present invention are as follows. (1) A magnetic circuit configuration assembly for a voice coil motor is provided, comprising: a pair of yokes; a pair of magnets, which are respectively arranged to contact the inner surfaces of the pair of yokes; and a supporting member, which maintains a gap between the pair of magnets and fixes the pair of yokes to each other, wherein the magnets are rare earth sintered magnets having a surface on which a coating is applied, and the rare earth sintered magnet has a composition consisting of: 28 wt % to 34 wt % of R (R is one or two or more types of rare earth elements selected from Nd, Pr, Dy, Tb, Ce, La and Gd), 2 wt % or less of Co, 0.5 wt % to 2 wt % of B, 2 wt % or less of At least one type of element selected from the group consisting of Ni, Nb, Al, Ti, Zr, Cr, V, Mn, Mo, Si, Sn, Ga, Cu and Zn as an additive, and the remainder of Fe and inevitable impurities, and the coating has a multilayer structure consisting of a metal electroplating layer and a metal oxide layer and / or a metal nitride layer in sequence from the rare earth sintered magnet side, the metal electroplating layer also has a multilayer structure consisting of a copper electroplating layer and a nickel electroplating layer in sequence from the rare earth sintered magnet side, the total thickness of the metal electroplating layer and the metal oxide layer and / or the metal nitride layer is 3μm to 80μm, and the thickness of the metal oxide layer and / or the metal nitride layer is 0.01μm to 2μm.

[0013] (2) A voice coil motor is provided, comprising: a magnetic circuit configuration assembly for the voice coil motor according to (1) above; and a coil located in a gap between a pair of magnets.

[0014] (3) A method for manufacturing a magnetic circuit configuration assembly for a voice coil motor is provided, the method comprising: A pair of plates is formed, the pair of plates being composed of a rare earth sintered magnet having a composition consisting of 28 wt % to 34 wt % of R (R is one or two or more types of rare earth elements selected from Nd, Pr, Dy, Tb, Ce, La and Gd), 2 wt % or less of Co, 0.5 wt % to 2 wt % of B, 2 wt % or less of at least one type of element selected from Ni, Nb, Al, Ti, Zr, Cr, V, Mn, Mo, Si, Sn, Ga, Cu and Zn as an additive, and a balance of Fe and inevitable impurities; surfaces of the pair of plates are copper plated, and the plated The copper surface is nickel plated to form a metal plating layer; a pair of plates on which the metal plating layer is formed are heat treated to oxidize and / or nitride the metal of the metal plating layer to form a metal oxide layer and / or a metal nitride layer, the total thickness of the metal plating layer and the metal oxide layer and / or the metal nitride layer is 3μm to 80μm, and the thickness of the metal oxide layer and / or the metal nitride layer is 0.01μm to 2μm; a pair of yokes are respectively adhered to a pair of plates on which the metal oxide layer and / or the metal nitride layer are formed; and the pair of yokes are fixed to each other using a supporting member so that the pair of plates adhered to the pair of yokes face each other and a gap is maintained between the pair of plates. Effects of the Invention

[0015] In this way, according to the present invention, by using a rare earth sintered magnet in which a coating is formed on the surface in a magnetic circuit configuration component for a voice coil motor as a pair of magnets, by setting the rare earth sintered magnet to have a predetermined composition, in which the coating has a multilayer structure consisting of a predetermined metal plating layer and a metal oxide layer and / or a metal nitride layer on the metal plating layer, by setting the total thickness of the metal plating layer and the metal oxide layer and / or the metal nitride layer within a predetermined range, and by setting the thickness of the metal oxide layer and / or the metal nitride layer within a predetermined range, even if the voice coil motor is exposed to a low-pressure hydrogen atmosphere for a long time, damage (such as chipping or cracking) can be prevented from occurring in the magnet, and deterioration of the magnetic properties of the magnet can be prevented. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is a schematic perspective view showing one embodiment of a magnetic circuit configuration assembly for a VCM according to the present invention. Figure 2 Viewed from arrow II Figure 1 Schematic front view of the magnetic circuit configuration components. Figure 3is a schematic perspective view showing another embodiment of a magnetic circuit configuration assembly for a VCM according to the present invention. Figure 4 It is viewed from arrow IV Figure 3 Schematic front view of the magnetic circuit configuration components. Figure 5 3 is a graph showing the measurement results of the flux of the sintered magnets of Example 1 and Comparative Example 1. Figure 6 Graph showing the demagnetization curve of the sintered magnet of Example 1. Figure 7 3 is a graph showing a demagnetization curve of the sintered magnet of Comparative Example 1. Figure 8 is a schematic plan cross-sectional view showing a magnetic circuit configuration assembly and a torque measurement assembly of a VCM for describing torque measurement. Fig. 9 is along Figure 8 Schematic side cross-sectional view of a magnetic circuit configuration assembly and a torque measurement assembly for a VCM, taken along line AA. Fig.10 3 is a graph showing the measurement results of the flux of the sintered magnets of Example 2 and Comparative Example 2. Fig.11 3 is a graph showing the measurement results of the flux of the sintered magnets of Example 3 and Comparative Example 3. Fig.12 : is a graph showing the torque measurement results of Example 4. Fig.13 is a graph showing the torque measurement results of Comparative Example 4. Fig.14 Graph showing the torque change rates of Example 4 and Comparative Example 4. DETAILED DESCRIPTION

[0017] Hereinafter, embodiments of a voice coil motor, a magnetic circuit configuration assembly for a voice coil motor, and a method of manufacturing the magnetic circuit configuration assembly according to the present invention will be described with reference to the accompanying drawings.

[0018] like Figure 1 and Figure 2 As shown, the magnetic circuit configuration component 10 for VCM according to the present embodiment is mainly configured with a pair of plate-like yokes 1, a pair of plate-like magnets 2 respectively arranged to contact the inner surfaces of the pair of plate-like yokes 1, and a plurality of pins 3 that maintain a gap between the pair of plate-like magnets 2 and fix the pair of plate-like yokes 1 to each other. The VCM can be set by installing a coil (not shown) in the gap between the pair of plate-like magnets 2 of the magnetic circuit configuration component 10.

[0019] exist Figure 1 and Figure 2In FIG. 1 , the entire yoke 1 is represented as a plate in a planar shape, and the yoke 1 may have uneven portions, steps, etc. in the peripheral portion of the contact surface with the magnet 2. Figure 1 and Figure 2 In the example of the case where the magnetic medium is a disk having a disk shape, the shape of the magnet 2 is drawn in an arc shape. In addition, the present invention is not limited to this, and the shape of the magnet 2 can be appropriately set to a desired shape according to the trajectory of the reciprocating motion of the VCM on the magnetic medium, etc. In addition, for example, in addition to the pair of plate-like yokes 1, a center yoke or a magnet fixed to the center yoke can be provided in the gap between the pair of plate-like magnets 2.

[0020] Furthermore, the magnetic circuit configuration assembly for VCM according to the present invention is not limited to Figure 1 and Figure 2 The embodiment shown, and may be, for example Figure 3 and Figure 4 Another embodiment shown in FIG. Figure 3 and 4 As shown, in a magnetic circuit configuration assembly 10A for VCM, a pair of plate-like yokes 1A and a pair of plate-like magnets 2A respectively arranged to contact the inner surfaces of the pair of plate-like yokes 1A have the same manner as described above. In addition, as a supporting member for maintaining a gap between the pair of plate-like magnets 2A and fixing the pair of plate-like yokes 1A to each other, a plurality of supporting columns 3A as curved yokes are provided.

[0021] The material of the yoke 1 is a material in the prior art, which is used for the yoke of a VCM, and for example, a cold rolled steel sheet (SPCC) material, a stainless steel material, etc. can be used without particular limitation.

[0022] The plate magnet 2 is attached to the inner surface of the plate yoke 1 by an adhesive (not shown). The adhesive is not particularly limited, and an adhesive with low outgassing is used from the viewpoint of preventing foreign matter from adhering to the actuator, etc. For example, an adhesive such as an acrylic-based adhesive or an epoxy-based adhesive is used.

[0023] The plate-like magnet 2 is a rare earth sintered magnet having a coated surface. The rare earth sintered magnet has a composition consisting of 28 wt % to 34 wt % of R (R is one or two or more types of rare earth elements selected from Nd, Pr, Dy, Tb, Ce, La and Gd), 2 wt % or less of Co, 0.5 wt % to 2 wt % of B, 2 wt % or less of at least one type of element selected from Ni, Nb, Al, Ti, Zr, Cr, V, Mn, Mo, Si, Sn, Ga, Cu and Zn as an additive, and the balance of Fe and inevitable impurities.

[0024] The coating on the surface of the rare earth sintered magnet has a multilayer structure consisting of a metal plating layer and a metal oxide layer and / or a metal nitride layer in order from the rare earth sintered magnet side. The metal plating layer further has a multilayer structure consisting of a copper plating layer and a nickel plating layer in order from the rare earth sintered magnet side. The metal oxide layer and / or the metal nitride layer is formed by heat treating the above-mentioned metal plating layer.

[0025] The number of metal plating layers is preferably 2 to 5. In addition, the total thickness of the metal plating layer and the metal oxide layer and / or the metal nitride layer is preferably set to 3 μm to 80 μm, and more preferably set to 5 μm to 60 μm. If the total thickness exceeds 80 μm, it takes time and is expensive, and efficient production cannot be performed, and the magnetic properties may be adversely affected. On the other hand, if the thickness is less than 3 μm, it is impossible to improve the impact resistance of the sintered magnet itself, thereby preventing chipping and the like, and unevenness in metal plating may occur, and pinholes may be formed, which may lead to insufficient formation of the metal oxide layer and / or the metal nitride layer.

[0026] The thickness of the metal oxide layer and / or the metal nitride layer is preferably 0.01 μm to 2 μm. If the thickness of the metal oxide layer and / or the metal nitride layer exceeds 2 μm, it takes time and is expensive, and effective production cannot be carried out, and the magnetic properties may be adversely affected. On the other hand, if the thickness is less than 0.01 μm, the role and function of the metal oxide layer and / or the metal nitride layer cannot be fully demonstrated. The thickness of the metal oxide layer and / or the metal nitride layer can be measured by analyzing the element concentration and chemical bonding state in the depth direction of the cross section of the magnet 2 by X-ray photoelectron spectroscopy (XPS).

[0027] In this way, by forming a surface coating of a metal plating layer and a metal oxide layer and / or a metal nitride layer on the surface of the rare earth sintered magnet, even if the VCM is exposed to a hydrogen atmosphere in a housing of a storage device (e.g., HDD) for a long time, damage (e.g., chipping or cracking) of the pair of magnets 2 can be prevented from occurring, and the magnetic properties of the pair of magnets 2 can be prevented from being deteriorated due to hydrogen exposure. Therefore, even if the interior of the housing is filled with hydrogen instead of helium, precise control of the actuator by the VCM can be maintained, and data can be accurately read from and written to the magnetic medium.

[0028] The material for using the magnetic circuit configuration component for VCM as the coil of VCM is a material in the related art, which is used for the coil of VCM. For example, copper or the like is preferably used, but is not particularly limited. Preferably, the coil is wound around one of the yoke 1 and the magnet 2 so as to be movable.

[0029] Next, a method for manufacturing a magnetic circuit configuration assembly for a VCM according to the present embodiment will be described. Since the magnetic circuit configuration assembly has been described, a detailed description thereof will be omitted here.

[0030] The manufacturing method of the magnetic circuit configuration component for VCM according to the present embodiment includes: (1) a step of forming a pair of plates composed of a rare earth sintered magnet having the above-mentioned composition, (2) a step of copper-plating the surfaces of the pair of plates and nickel-plating the copper-plated surfaces to form a metal plating layer, (3) a step of heat-treating the pair of plates having the metal plating layer to form a metal oxide layer and / or a metal nitride layer, (4) a step of respectively adhering a pair of yokes to a pair of plates having the metal oxide layer and / or the metal nitride layer, and (5) a step of fixing a pair of yokes to each other using a supporting member so that the pair of plates adhered to the pair of yokes face each other and a gap is maintained between the pair of plates. Each step will be described in detail.

[0031] In the step of forming a pair of plates, first, an alloy having the above composition is cast, the alloy is pulverized, and more preferably, finely pulverized, and then the alloy is sequentially formed in a magnetic field, sintered, and heat treated to produce a sintered magnet.

[0032] More specifically, the raw material with the above composition is dissolved by high frequency dissolution in a non-oxidizing atmosphere (e.g., argon), and cast. Next, the alloy is roughly crushed, and then crushed to an average particle diameter preferably of 1 μm to 10 μm, but is not particularly limited. Roughly crushing can be carried out, for example, by a jaw crusher, a Brown mill, a pin mill, hydrogen absorption, etc. in an inert gas atmosphere. In addition, crushing can be carried out by a wet ball mill or a grinding mill using ethanol, hexane, etc. as a solvent, a dry ball mill in an inert gas atmosphere, a jet mill using an inert gas stream, etc.

[0033] Next, by being able to preferably 200kg / cm 2 or greater and less than 2000kg / cm 2 The finely pulverized powder is compression molded by a magnetic field press or the like which applies a magnetic field of preferably 10 kOe or more, particularly 15 kOe or more, under a pressure of 1.5 kOe. Subsequently, the obtained compression molded product is sintered in a heat treatment furnace at 1000° C. to 1200° C. for 1 to 2 hours in a high vacuum or non-oxidizing atmosphere gas (e.g., argon).

[0034] Subsequently, heat treatment is performed at a temperature lower than the sintering temperature, preferably at a temperature of 400°C to 700°C, in a vacuum or a non-oxidizing atmosphere gas (e.g., argon) to obtain a sintered magnet. The sintered magnet obtained in this manner is cut into a pair of plates having a predetermined shape and polished for surface treatment. At this time, beveling is preferably performed on the rare earth sintered magnet body, but is not particularly limited.

[0035] In the step of forming a metal plating layer, n (n is an integer) layers of metal plating layers are formed on a pair of plates of a rare earth sintered magnet. Here, as the number of metal plating layers increases, corrosion resistance is improved. Therefore, n is selected according to the corrosion resistance or other conditions required for the application. In addition, considering manufacturing, cost and efficiency, n is 2 to 5. The metal of the metal plating layer is composed of Cu or Ni, and the plating thickness is 3μm to 80μm, and particularly preferably 5μm to 50μm. More specifically, multilayer plating is a multilayer plating in which Cu is formed on the lower layer and Ni is further formed thereon. There is no particular restriction on the pretreatment before metal plating, and it is preferred that a pair of plates be alkali degreased, pickled and washed with water. There is no particular restriction on the method for forming the electroplated film, and the electroplating method is ideal. In addition, the method of immersing a pair of plates in the plating solution can be any one of a barrel immersion method or a hanging fixture method, and can be appropriately selected according to the size and shape of a pair of plates.

[0036] As the plating solution, a known plating solution having a known composition can be used, and plating can be performed under known conditions according to the plating solution, and a plating solution having a pH of 2 to 12 is particularly suitable. In addition, in the case where two or more metal layers having different compositions are laminated, it is sufficient that the immediately lower layer has a more inert corrosion potential (nobler corrosion potential) relative to the uppermost layer. In addition, in the method of controlling the potential by changing the sulfur content in the film, such as in the case of a double-layer Ni plating layer, the sulfur content of the upper layer is set to about 0.03% or less, and the lower layer may be free of sulfur.

[0037] In the step of forming the metal oxide layer and / or the metal nitride layer, the pair of plates on which the metal plating layer is formed may be subjected to heat treatment in an atmosphere (e.g., air, under oxygen partial pressure adjustment, under nitrogen, or under high-pressure nitrogen) to oxidize or nitride the metal of the metal plating layer, thereby forming a metal oxide layer or a metal nitride layer. More specifically, in the case of forming the metal oxide layer, for example, it is preferred to heat the metal plating layer in an atmosphere of 10 -4The heat treatment is performed at 200°C to 600°C for 3 to 50 hours in an argon, nitrogen, air or low-pressure vacuum atmosphere of 100 kPa to 50 kPa. The total thickness of the metal plating layer and the metal oxide layer and / or the metal nitride layer is 3 μm to 80 μm, and the thickness of the metal oxide layer and / or the metal nitride layer is 0.01 μm to 2 μm. The thickness of the metal oxide layer and / or the metal nitride layer can be measured by X-ray photoelectron spectroscopy (XPS) as described above.

[0038] like Figures 1 to 4 As shown, in the step of adhering a pair of yokes to a pair of plates, a pair of plates on which a metal oxide layer and / or a metal nitride layer is formed are adhered to the inner surface of each yoke of a pair of yokes 1 and a pair of yokes 1A. Due to the above description, an adhesive for bonding will not be described here.

[0039] In the step of fixing the pair of yokes to each other, as Figures 1 to 4 As shown, for example, a plurality of pins 3 or a plurality of support columns 3A as a curved yoke are used as a support member to fix a pair of yokes 1 and a pair of yokes 1A to each other, so that a pair of plate-like magnets 2 and a pair of plate-like magnets 2A adhered to a pair of plate-like yokes 1 and a pair of plate-like yokes 1A face each other, and a gap is maintained between the pair of plates. Therefore, it is possible to manufacture a magnetic circuit configuration assembly 10 and 10A for a voice coil motor, the magnetic circuit configuration assembly 10 and 10A including a pair of plate-like magnets 2 and a pair of plate-like magnets 2A composed of a rare earth sintered magnet having a predetermined composition and having a predetermined coating on the surface. Example

[0040] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples, and the present invention is not limited thereto.

[0041] Example 1 First, a magnet alloy is produced by mixing the following components: Nd+Pr: 29.5 wt.%, Co: 0.5 wt.%, B: 0.9 wt.%, Al, Cu, Zr and Ga as additives with a total weight of 0.65 wt.%, and the balance of Fe, and dissolving the mixture in a high-frequency melting furnace using an alumina crucible and casting the mixture in a mold in an argon atmosphere.

[0042] Next, the magnet alloy was coarsely pulverized to about 500 μm or less by using a jaw crusher and a Brown mill, and then finely pulverized to an average particle diameter of about 3 μm by using a jet mill with a nitrogen gas flow. 2The obtained fine pulverized powder was molded in a magnetic field of 10 kOe under a pressure of 100 ℃. The obtained molded product was sintered at 1070 ℃ for 2 hours in an argon atmosphere by using a heat treatment furnace, cooled, and then further heat-treated at 600 ℃ for 1 hour in an argon atmosphere to produce a sintered magnet. The obtained sintered magnet was cut into an arc-shaped plate having the same shape as that of a magnet for VCM.

[0043] Electrolytic Cu plating (10 μm) and electrolytic Ni plating (10 μm) were sequentially applied to the curved plate. In this case, the electroplating bath was adjusted with 60 g / L copper pyrophosphate, 240 g / L potassium pyrophosphate and 30 g / L potassium oxalate at a bath temperature of 40°C and 1.5 A / dm 2 The electrolytic Cu plating was carried out under the condition of current density of 2.0A / dm, and then the electroplating bath was adjusted with 40g / L nickel chloride, 270g / L nickel sulfate and 30g / L boric acid at a bath temperature of 50°C and a current density of 2.0A / dm 2 Electrolytic Ni plating was performed under the condition of a current density of . Thereafter, heat treatment was performed in air at 350° C. for 10 hours, and the curved plate was slowly cooled to room temperature to obtain a test sample (Example 1).

[0044] Comparative Example 1 In addition, as a comparison, another test sample was obtained in the same manner as in Example 1, except that electrolytic Cu plating (10 μm) and electrolytic Ni plating (10 μm) were sequentially performed on the curved plate, and no heat treatment was performed (Comparative Example 1), which is different from Example 1 in which electrolytic Cu plating (10 μm) and electrolytic Ni plating (10 μm) were sequentially performed on the curved plate and then heat treatment was performed.

[0045] Hydrogen exposure test Each test sample of Example 1 and Comparative Example 1 was placed in a pressure-resistant container and exposed to a hydrogen atmosphere (0.29 MPa and 100° C.) for 7 days, and the flux (total magnetic flux), demagnetization curve, and torque in the rotation direction of the swing arm of the voice coil motor were measured after 4 days of hydrogen exposure, 5 days of hydrogen exposure, 6 days of hydrogen exposure, and 7 days of hydrogen exposure, and the appearance and cross-sectional structure of the test sample were observed before hydrogen exposure. The flux and demagnetization curve were measured for two test samples of each of Example 1 and Comparative Example 1.

[0046] The flux was measured by using a flux meter (manufactured by Magnet-Force Co., Ltd., model TFM-2000) to measure the flux (unit: WB·T). As a detection coil, a coil of 70 μm diameter copper wire x 100 turns was used. The measurement results of the flux of Example 1 and Comparative Example 1 are shown in Figure 5 middle.

[0047] In the demagnetization curve, as the magnetic properties of the test sample, the residual magnetic flux density Br (unit: T), the intrinsic coercive force HcJ (unit: Ka / m), the coercive force HcB (unit: Ka / m) and the maximum energy product (BH) maximum value (kJ / m) were measured by using a vibrating sample magnetometer (manufactured by RikenDenshi Co., Ltd.) 3 ). Then, based on these measurements, a JH curve is obtained, in which the magnetic field H is plotted on the horizontal axis and the magnetization intensity J is plotted on the vertical axis. Figure 6 and Figure 7 Demagnetization curves (JH curves) of Example 1 and Comparative Example 1 are respectively shown.

[0048] like Figure 8 and Fig. 9 As shown, by producing a magnetic circuit configuration assembly 10 for a VCM using a test sample as a magnet 2 and attaching a torque measurement assembly 20 to the magnetic circuit configuration assembly 10 , the torque in the rotation direction of the swing arm is measured. Fig. 9 is along Figure 8 A side cross-sectional view of the magnetic circuit configuration assembly 10 and the torque measurement assembly 20 for a VCM taken along line AA is shown, and Figure 8 is along Fig. 9 The plane cross-sectional view of the magnetic circuit configuration assembly 10 and the torque measurement assembly 20 for VCM is shown along line BB. Figure 8 In the figure, for the clarity of the drawing, the magnet 2 is omitted in the magnetic circuit configuration assembly 10 for VCM. Since the magnetic circuit configuration assembly 10 for VCM has been described, the description thereof will be omitted here.

[0049] The torque measuring assembly 20 includes: a main body 21 having a rotating shaft 23; a swing arm 22 having a through hole for passing the rotating shaft 23 on the center line and having a tip portion divided into two; an air-core coil 25 sandwiched between the tip portions divided into two of the swing arm 22; an angle sensor (not shown) for measuring the angle of the swing arm 22; and a torque sensor (not shown) for measuring the torque in the rotation direction of the swing arm 22. The swing arm 22 is rotatably supported by the rotating shaft 23. An end 24 of the main body 21 on the side opposite to the swing arm 22 has a comb shape. The magnetic circuit configuration assembly 10 for VCM here is a magnetic circuit for VCM in which a magnet 2 is attached to a yoke 1, and then a tip surface 2-pole magnetization is performed by setting the center of the magnet 2 to the center of the neutral region (the center of the boundary region of the magnetic pole) in the radial direction.

[0050] In the torque measurement, the swing arm 22 of the torque measuring assembly 20 rotates while current flows through the air-core coil 25 through a constant voltage power supply (not shown), and the values ​​of the angle sensor and the torque sensor of the torque measuring assembly 20 are read to measure the torque at each angle of the swing arm. In the measurement, if the position of the center line of the swing arm 22 is located at the center of the neutral area of ​​a pair of magnets 2 magnetized to two poles, respectively, it is defined as an angle of 0°. In addition, in the measurement, the current is made to flow in two directions, namely, the positive direction and the negative direction, and the average value of the absolute value of the current is used as the torque value at the angle.

[0051] The observation of the appearance of the test sample was performed by visual observation. In addition, the cross-sectional structure of the test sample was observed with a scanning electron microscope (manufactured by JEOL Ltd.).

[0052] As a result of observing the appearance of the test samples, in Example 1, no damage (such as chipping and cracking) was detected in any of the test samples after hydrogen exposure. Figure 5 As shown, the flux of Example 1 remains at about 310 x 10 -5 The values ​​of Wb / T were measured before hydrogen exposure (day 0) and even after 7 days had passed since hydrogen exposure. Figure 6 As shown, even after 7 days of hydrogen exposure, the demagnetization curve (JH curve) maintains the same verticality as that before hydrogen exposure (0 day).

[0053] On the other hand, in Comparative Example 1 in which heat treatment was not performed after metal plating, since a large number of test samples were used in the hydrogen exposure test, it was found that 4% of the test samples were damaged by chipping, cracking, etc. after 4 days of hydrogen exposure, 15% of the remaining test samples were damaged after 5 days of hydrogen exposure, 54% of the remaining test samples were damaged after 6 days of hydrogen exposure, and 36% of the remaining test samples were damaged after 7 days of hydrogen exposure. In this way, by forming a metal oxide through heat treatment after metal plating in Example 1, damage (such as chipping, cracking, etc.) can be prevented from occurring in the magnet.

[0054] In addition, in the flux of Comparative Example 1, Figure 5 As shown, even when measured on a test sample without damage, the flux before hydrogen exposure (0 day) was approximately 310 x 10 -5 Wb / T decreased to about 280x 10 after 4 days of hydrogen exposure. -5 Wb / T to 290x 10 -5 Wb / T decreased to about 270x 10 after 5 days of hydrogen exposure. -5 Wb / T to 280x 10 -5 Wb / T.

[0055] In addition, regarding the demagnetization curve (JH curve), Figure 7 As shown in FIG. 1 , even in Comparative Example 1 in which the magnetic properties of the test sample without damage were measured, the test sample could not maintain the verticality of the test sample before the hydrogen exposure after the hydrogen exposure. If current flows through the coil in the magnetic field of the magnet, the VCM causes the actuator to reciprocate by utilizing the generation of a force in a direction perpendicular to both the magnetic field and the current according to Fleming's left-hand rule. Since the actuator is precisely controlled by generating a thrust proportional to the energized current, if the magnetic properties of the magnet are affected by the force generated by the VCM, the actuator will be reciprocated. Figure 7 If the hydrogen exposure shown deteriorates and the constant magnetization J cannot be maintained within a predetermined range of the magnetic field H, the actuator cannot be accurately controlled and data cannot be read or written.

[0056] In the test sample of Comparative Example 1 which was exposed to hydrogen for 4 to 7 days and was not damaged, the cross-sectional structure was observed, and as a result, no abnormality was particularly found in the Ni plating layer on the surface or in the magnet below the Ni plating layer. In addition, as a result of observing the cross-sectional structure of the test sample of Example 1 after 4 to 7 days of hydrogen exposure, no abnormality was particularly found in the metal oxide layer on the surface, the Ni plating layer, the Cu plating layer, and the magnet below the metal oxide layer.

[0057] In addition, a test sample of the magnet alloy was produced by performing electrolytic Cu plating (10 μm) and electrolytic Ni plating (10 μm) in sequence in the same manner as in Example 1, and heat treating the following components in air at 300°C x 20 hours in Example 2 and at 400°C x 5 hours in Example 3, respectively: Instead of the components of the magnet alloy of Example 1, the components in Example 2 are: Nd+Pr: 28.5 wt.%, Dy: 1.0 wt.%, Co: 0.5 wt.%, B: 0.9 wt.%, a total of 0.60% Al, Cu, Zr and Ga as additives, and the balance Fe, and the components in Example 3 are: Nd+Pr: 33.0 wt.%, Co: 0.5 wt.%, B: 1.0 wt.%, a total of 0.75% Al, Cu, Zr and Ga as additives, and the balance Fe. Furthermore, as a comparison, the above magnet alloy was subjected to an electroplating process in the same manner as in Comparative Example 1 to obtain test samples of Comparative Examples 2 and 3.

[0058] The test samples of Examples 2 and 3 and Comparative Examples 2 and 3 were subjected to the same hydrogen exposure test as described above, and the flux was measured. Fig.10 The measurement results of the flux of Example 2 and Comparative Example 2 are shown. Fig.11 The measurement results of the flux of Example 3 and Comparative Example 3 are shown. Fig.10 and Fig.11 As shown, for the compositions of the magnet alloys of Examples 2 and 3, the same results as those of the magnet alloy of Example 1 were obtained.

[0059] Furthermore, if the thickness of the metal oxide layer on the surface of the test sample of Example 1 was measured by using an X-ray photoelectron spectroscopy apparatus (manufactured by Shimadzu Kratos Inc, AXIS-HSI), the thickness was about 0.05 μm.

[0060] A magnetic circuit configuration component for VCM was manufactured by using a test sample (Example 4) produced by the same procedure as in Example 1, and in which a pair of rare earth magnets were magnetized to two poles respectively in a magnetic field of 3 T, and the torque was measured as described above. The hydrogen exposure conditions of the test sample were also the same as in Example 1, and the test sample was produced and measured by using each hydrogen exposure condition. The results are shown in Fig.12 In. Fig.12 As shown, even after 7 days of hydrogen exposure, the torque at any angle remained the same as the torque before hydrogen exposure (0 day).

[0061] By using a test sample (Comparative Example 4) produced by the same procedure as in Comparative Example 1 and in which a pair of rare earth magnets were magnetized to two poles in a magnetic field of 3 T, the torque was measured in the same manner as in Example 4. The results are shown in Fig.13 In. Fig.13 As shown, in Comparative Example 4, the torque is reduced at any angle according to the exposure time in hydrogen.

[0062] In order to analyze the maintenance and reduction of torque more closely, the maximum value of the torque at each exposure time was obtained from the torque measurement results of Example 4 and Comparative Example 4, and the change rate of the maximum value of the torque before and after exposure was calculated (the maximum value of the torque before exposure was set to 100). The results are shown in Fig.14 In. Fig.14 As shown, in Comparative Example 4, the torque decreased as the exposure time increased, and a decrease of 4.4% was observed in 7 days of exposure. On the other hand, in Example 4, no decrease in torque was observed.

[0063] In this way, it has been examined that damage (such as chipping and cracking) due to hydrogen exposure can be reliably prevented by performing heat treatment after metal plating of the magnet to form a metal oxide on the surface, and it has been found that damage (such as chipping and cracking) can be reduced to a certain extent even with only metal plating. In addition, even if such damage does not occur, it has been confirmed that in the comparative example having only the metal plating layer, the magnetic properties of the magnet deteriorate and the magnet cannot be used as a magnet for VCM. Reference Symbols List

[0064] 1.1A: Yoke 2.2A: Magnet 3: Pin 3A: Support column for curved yoke 10, 10A: Magnetic circuit configuration components for voice coil motors (VCMs) 20: Torque measurement components 22: Swing arm 23: Rotation axis 25: Hollow coil

Claims

1. A magnetic circuit configuration assembly for a voice coil motor, comprising: a pair of yokes; a pair of magnets respectively disposed in contact with inner surfaces of the pair of yokes; and a supporting member that maintains a gap between the pair of magnets and fixes the pair of yokes to each other, wherein the magnet is a rare earth sintered magnet having a surface on which the coating is applied, The rare earth sintered magnet has a composition consisting of 28 wt % to 34 wt % of R (R is one or two or more types of rare earth elements selected from Nd, Pr, Dy, Tb, Ce, La and Gd), 2 wt % or less of Co, 0.5 wt % to 2 wt % of B, 2 wt % or less of at least one type of element selected from Ni, Nb, Al, Ti, Zr, Cr, V, Mn, Mo, Si, Sn, Ga, Cu and Zn as an additive, and the balance of Fe and inevitable impurities, and The coating has a multilayer structure consisting of a metal electroplating layer and a metal oxide layer and / or a metal nitride layer in sequence from the rare earth sintered magnet side, the metal electroplating layer also has a multilayer structure consisting of a copper electroplating layer and a nickel electroplating layer in sequence from the rare earth sintered magnet side, the total thickness of the metal electroplating layer and the metal oxide layer and / or the metal nitride layer is 3μm to 80μm, and the thickness of the metal oxide layer and / or the metal nitride layer is 0.01μm to 2μm.

2. Voice coil motor, including: The magnetic circuit configuration assembly for a voice coil motor according to claim 1; and A coil is located in the gap between the pair of magnets.

3. A method for manufacturing a magnetic circuit configuration assembly for a voice coil motor, the method comprising: forming a pair of plates composed of a rare earth sintered magnet having a composition consisting of 28 wt % to 34 wt % of R (R is one or two or more types of rare earth elements selected from Nd, Pr, Dy, Tb, Ce, La and Gd), 2 wt % or less of Co, 0.5 wt % to 2 wt % of B, 2 wt % or less of at least one type of element selected from Ni, Nb, Al, Ti, Zr, Cr, V, Mn, Mo, Si, Sn, Ga, Cu and Zn as an additive, and the balance of Fe and inevitable impurities; Electroplating the surfaces of the pair of plates with copper, and electroplating the copper-plated surfaces with nickel to form a metal electroplating layer; heat-treating the pair of plates on which the metal electroplating layer is formed to oxidize and / or nitride the metal of the metal electroplating layer to form a metal oxide layer and / or a metal nitride layer, wherein the total thickness of the metal electroplating layer and the metal oxide layer and / or the metal nitride layer is 3 μm to 80 μm, and the thickness of the metal oxide layer and / or the metal nitride layer is 0.01 μm to 2 μm; adhering a pair of yokes to the pair of plates on which the metal oxide layer and / or the metal nitride layer are formed, respectively; and The pair of yokes are fixed to each other using a supporting member so that the pair of plates adhered to the pair of yokes face each other with a gap maintained between the pair of plates.

Citation Information

Patent Citations

  • Sintered rare-earth magnet

    JP2003257721A

  • Manufacturing method for rare earth sintered magnet

    JP2003257768A

  • Magnetic disk drive and control method thereof

    JP2009140524A

  • Tape embedded drive

    JP2020129424A